ISOLATION, CHARACTERIZATION AND STRAIN IMPROVEMENT OF SOIL BACTERIA Bacillus Subtilis FOR INVERTASE PRODUCTION - KAUR, MANMEET; TEOTIA, PRATIBHA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Enzyme invertase used to hydrolyse sucrose is used in many industries preparing drink, confectionary, bakery, invert sugar, fructose syrup, calf feed and food for honeybees along with several other applications. The extensive uses of the enzyme require their new sources which can tolerate the severe industrial processes. The invertase of improved features to work in extreme industrial process is need of the time. The present investigation deals with isolation of soil bacteria from soil having history of continuous discording of fruits waste. The bacterial isolates identified as Bacillus subtilis. The bacteria performed well naturally further subject to strain improvement by physical and chemical mutagenesis resulted in enhanced invertase activity. The strain performs well between pH 6-11 with optimum at pH 7.